Serum Trans Fatty Acids Are Not Associated with Weight Gain or Linear Growth in School-Age Children(1)(2)(3) - Baylin, Ana (J Nutr, 2015)
Background: Animal and human adult studies indicate that long-term intake of trans fatty acids (TFAs) may be associated with weight gain. High intake of fast foods and snacks, which are rich in TFAs, is linked to overweight status among school-age children. However, the specific effects of TFAs in this population are unknown. Objective: We examined whether serum TFAs, used as biomarkers of intake, are associated with faster weight gain and linear growth during school years. Methods: We quantified TFAs by GLC in serum samples of 668 children aged 5–12 y at the time of recruitment into an ongoing cohort study performed in Bogota (Colombia) since 2006. Serum proportions of trans palmitoleic acid (16:1t), trans oleic acid (18:1t), trans linoleic acid (18:2t), and total TFAs were used as biomarkers of intake. Anthropometric characteristics were measured periodically for a median of 30 mo. Body mass index-for-age z scores (BAZs) and height-for-age z scores (HAZs) were calculated with the use of the WHO reference. We estimated mean changes in BAZs and HAZs over follow-up according to quartiles of each TFA at baseline by using mixed-effects regression models with restricted cubic splines. Results: Proportions of trans palmitoleic acid, trans oleic acid, trans linoleic acid, and total TFAs (mean ± SD, % of total serum FAs), were 0.22 ± 0.06, 0.91 ± 0.37, 0.96 ± 0.27, and 2.10 ± 0.59, respectively. Serum TFAs were not associated with changes in BAZs and HAZs after adjusting for sex, baseline age, and socioeconomic status. In a subgroup analysis by sex, serum trans palmitoleic acid was positively associated with the estimated change in HAZs from ages 6 to 14 y in boys (with use of the first quartile as the reference, differences in HAZs for trans palmitoleic acid quartiles were 0.73, 0.53, and 0.70, P-trend = 0.03). Conclusions: Proportions of serum TFAs, used as biomarkers of TFA intake, were not associated with weight gain in children aged 6–14 y in low- and middle-income populations in Bogota. The proportion of trans palmitoleic acid was positively associated with linear growth in boys. Longer follow-up and studies in diverse cohorts with wider ranges of TFA intake are warranted.